Instructional Design Using the Dick & Carey Systems Approach - Tyler D'Angelo; James C. Bunch; Andrew C. Thoron (EDIS)
Instructional design is a system of procedures used for developing instruction and training curricula in a consistent and reliable method. This 5-page publication applies the best practices of instructional design using the Dick and Carey systems approach. Written by Tyler D’Angelo, J. C. Bunch, and Andrew Thoron and published by the UF/IFAS Department of Agricultural Education and Communication, March 2018. http://edis.ifas.ufl.edu/wc294